Decisions during Negatively-Framed Messages Yield Smaller Risk-Aversion-Related Brain Activation in Substance-Dependent Individuals - Fukunaga, Rena (2012)
A sizable segment of addiction research investigates the effects of persuasive message appeals on risky and deleterious behaviors. However, to date, little research has examined how various forms of message framing and corresponding behavioral choices might by mediated by risk-related brain regions. Using event-related functional magnetic resonance imaging, we investigated brain regions hypothesized to mediate the influence of message appeals on decision making in substance-dependent (SD) compared to non-substance-dependent (non-SD) individuals. The Iowa Gambling Task (IGT) was modified to include positively-framed, negatively-framed, and control messages about long-term deck payoffs. In the positively-framed condition, the SD and non-SD groups showed improved decision-making performance that corresponded to higher risk-aversion-related brain activity in the anterior cingulate cortex (ACC) and anterior insula (AI). In contrast, in the negatively-framed condition, the SD group showed poorer performance that corresponded to lower risk-aversion-related brain activity in the AI region. In addition, only the non-SD group showed a positive association between decision quality and greater risk-related activity in the ACC, regardless of message type. The findings suggest substance-dependent individuals may have reduced neurocognitive sensitivity in the ACC and AI regions involved in risk perception and aversion during decision-making, especially in response to framed messages that emphasize reduced prospects for long-term gains.